Judge Consistency and Severity across Grading Periods - Lunz, Mary E; Stahl, John A (Evaluation & the health professions, 1990)
Examinations were analyzed using the Rasch model to determine differences in judge severity and grading period stringency for (1) essay examination (subjects were 12 judges and 32 examinees); (2) clinical examination (subjects were 18 judges and 217 examinees); and (3) oral examination (subjects were 46 judges and 270 examinees). (SLD)